Time budgets of dairy cows in cow-calf contact system with automatic milking - Johansson, Teresa (2021)
Time budgets of dairy cattle are useful to determine the amount of time the cows can allocate to all the behaviours throughout the day. In an automatic milking system (AMS), time budgets are of interest as the individuals are able to choose how to spend the majority of their time, besides the time in the milking robot, and can be used to ensure adequate amounts of time are spent on essential behaviours, such as lying and eating. Keeping the calf together with the cow after parturition is also gaining interest in the dairy industry and from consumers’ point of view. Earlier research, without calves’ present, has shown that the cows time budget; how much time they place on different activities, such as eating, resting, and waiting their turn for the milking robot, can in some cases be quite strained. Thus, the aim of this study was to determine how the addition of calves into a loose housing system with AMS impacts the time budgets of dairy cows. The study included a literature review, a time budget study, and analysis of data collected from the Swedish livestock research center, Lövsta SLU in Uppsala. The study included 40 cow calf pairs, of the Swedish Red Breed and Holstein, housed in an AMS at Lövsta. The cow-calf pairs were divided into the treatment group, cow calf contact post parturition and the control group, separation post parturition. The results of the study showed that there was a significant difference between the treatment and control group in the time spent on the behaviours: eating roughage, eating concentrates, waiting at the AMS, standing in a free stall, and lying in a stall. Other factors, such as differences in the lactation the cow was in, the breed of the cow, and the period of the study also had an effect on the time spent on certain behaviours. While there were differences seen in the amount of time spent on some of the behaviours, both the treatment group and control group were able to perform essential behaviours, lying and eating for adequate amounts of time for their well-being and production. Thus, from our results having the calves present in the loose housing system with an AMS is feasible for farmers. However, more research in the area needs to be done to further investigate the impacts of having cow-calf contact systems on both the dam and the calves.